Manajemen Pembelajaran Berbasis Blended Learning Pada Masa Pandemi Covid-19 - Hindu, Hindu; Musyaffa, Musyaffa (JURNAL INOVASI EDUKASI, 2022)
During the Covid-19 Pandemic, Islamic educational institutions carried out distance learning online. For areas that are included in the green zone, face-to-face learning can be done with a limited time and in accordance with health protocols. One of the learning innovations that can be carried out by educational institutions is blended learning-based learning, including at Ma'ad Ali Pondok Pesantren As’ad adjoining Jambi City. This study aims to determine learning planning, implementation of learning, and evaluation of blended learning-based learning at Ma'ad Ali Pondok Pesantren As’ad, Jambi City. This study uses a qualitative approach with a descriptive method. Data were obtained through observation, interviews, and documentation studies. The results showed that at the planning stage, Ma'ad Ali Pondok Pesantren As’ad Jambi City with a blended learning model during the Covid-19 pandemic was supported by existing facilities and infrastructure. In the implementation phase, Ma'ad Ali Pondok Pesantren As’ad Jambi City applies a group division system. There are groups that are offline and some are learning online. However, conditions changed very quickly, Jambi became a red zone so it was not allowed to carry out face-to-face learning. In the evaluation stage, Ma'ad Ali Pondok Pesantren As’ad Jambi City conducted an online evaluation based on a website.